2018
DOI: 10.1177/2158244018803139
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into How Motivational Factors Differed Among Individuals Engaging in CrossFit Training

Abstract: With few adults completing recommended levels of aerobic and muscle-strengthening activities, it is important to examine the motives of those who do, as well as how those motives might differ by participation frequency. Considering the rapid growth of CrossFit Training (CFT), we examined CFT participation motives in individuals training at different frequencies. Adults (N = 732) with >3 months of CFT experience completed an online version of the Exercise Motivations Inventory-2 (EMI-2). Significant correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Women were more likely to place greater emphasis on factors related to stress, weight management, and appearance compared to men, who placed greater importance on factors associated with challenge, social recognition, competition, strength and endurance, and nimbleness 16/72.7 Sibley and Bergman [ 9 ] Motivation 322 Participants 65.2% Men 33.9 Results showed that CrossFit participants primarily strive for goals related to health management and skill development, with physique enhancement and social affiliation being of secondary importance. The most frequent participants in CrossFit had significantly higher levels of basic needs satisfaction (autonomy, relatedness and competency) 13/59.1 Feito et al [ 50 ] Motivation 732 Participants 388 men and 344 women 32.3 The results showed that individuals training < 3 days/week scored lowest on enjoyment, affiliation, and competition motives. Those training > 5 days/week scored highest on challenge, social recognition, strength and endurance, and nimbleness motives, but lowest on weight management 18/81.8 Ayar [ 51 ] Motivation 200 Participants 161 men and 39 women Do not report Differences have been found between motivation factors that affect individuals to participate in recreative sports and some of the demographical parameters in some variables of REMM’s health, rivalry, physical appearance, social/entertainment and skill development sub-dimensions Male participants attend to exercises in CrossFit centers with competitive reasons more than female participants 8/36.3 Marin et al [ 52 ] Motivation 493 Participants 493 351 men and 148 women 30.3 Participants: 365 traditional resistance training and 128 CrossFit CrossFit participants presented higher levels of enjoyment, stress management, social recognition, affiliation, competition, and weight management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women were more likely to place greater emphasis on factors related to stress, weight management, and appearance compared to men, who placed greater importance on factors associated with challenge, social recognition, competition, strength and endurance, and nimbleness 16/72.7 Sibley and Bergman [ 9 ] Motivation 322 Participants 65.2% Men 33.9 Results showed that CrossFit participants primarily strive for goals related to health management and skill development, with physique enhancement and social affiliation being of secondary importance. The most frequent participants in CrossFit had significantly higher levels of basic needs satisfaction (autonomy, relatedness and competency) 13/59.1 Feito et al [ 50 ] Motivation 732 Participants 388 men and 344 women 32.3 The results showed that individuals training < 3 days/week scored lowest on enjoyment, affiliation, and competition motives. Those training > 5 days/week scored highest on challenge, social recognition, strength and endurance, and nimbleness motives, but lowest on weight management 18/81.8 Ayar [ 51 ] Motivation 200 Participants 161 men and 39 women Do not report Differences have been found between motivation factors that affect individuals to participate in recreative sports and some of the demographical parameters in some variables of REMM’s health, rivalry, physical appearance, social/entertainment and skill development sub-dimensions Male participants attend to exercises in CrossFit centers with competitive reasons more than female participants 8/36.3 Marin et al [ 52 ] Motivation 493 Participants 493 351 men and 148 women 30.3 Participants: 365 traditional resistance training and 128 CrossFit CrossFit participants presented higher levels of enjoyment, stress management, social recognition, affiliation, competition, and weight management.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that more autonomous forms of motivation appeared in CrossFit training participants, so the motivational characteristics indicated an autonomous form of extrinsic motivation (identified as integrated regulations, and by intrinsic regulation). Therefore, people engaged in CrossFit training may achieve such goals as enhancing their own identities through exercise [ 7 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though attrition rates for intervention studies can be difficult to quantify [ 41 ], most studies that achieve low attrition rates, include additional components such as behavioral training (e.g., goal setting, mastery; [ 42 ]), weekly behavioral sessions and exercise logs [ 43 ], bi-weekly phone calls [ 44 ] and exercise self-monitoring in the form of detailed daily logs [ 45 ], which tend to be cumbersome for the participant and impractical in a “real world” scenario. Recently, several investigations from our laboratory have elucidated on the motivational factors that affect HIFT participation [ 46 , 47 , 48 ] and suggest this type of group-based training that includes constant personal challenges and competition seem to be motivating for most adults. Further studies should be conducted with larger samples to further investigate the effects of HIFT on body composition and glucose control for overweight and obese adults.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fitness-related motives have been reported among various HIFT participants as being important for exercise engagement regardless of sex [ 23 , 24 ]. More recently, Feito et al [ 25 ] demonstrated that fitness related motives differed among HIFT participants dependent upon their weekly training participation, with those training more often (>5 days/week) having significantly higher fitness-related motives compared to those engaged less often (<3 days/week). Nonetheless, less is understood about the changes in exercise motivation as it relates to beginning and continuing HIFT.…”
Section: Discussionmentioning
confidence: 99%